PECULIARITIES OF STRUCTURAL CHANGES IN COPPER AT DYNAMIC ALLOYING - E. I. Marukovich; Yu. S. Usherenko (Литьë и металлургия)
The peculiarities of the structural modifications in copper initiated by the processes of dynamic influence and ultradeep penetration of microparticles are studied.